2023
DOI: 10.9734/jemt/2023/v29i11074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Environment and Work-life Balance on Job Satisfaction: Work Stress as a Mediator

Abstract: Aims: Employees are one of the crucial factors in a company. Company must be able to pay attention to the physical and mental needs of the employee to obtain good performance. Work environment and work-life balance are the factors that affect the employees’ performance and job satisfaction. This research aims to identify the effect of the work environment and work-life balance on the job satisfaction of the employee’s millennial generation which is mediated by stress. Study Design:  Explanatory Research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The results of this research are in line with research by Jessica et al, (2023) which states that the work environment has a negative effect on employee work stress. The more conducive the employee's work environment is, the more it will reduce employee stress at work.…”
Section: The Work Environment Influences Work Stresssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this research are in line with research by Jessica et al, (2023) which states that the work environment has a negative effect on employee work stress. The more conducive the employee's work environment is, the more it will reduce employee stress at work.…”
Section: The Work Environment Influences Work Stresssupporting
confidence: 89%
“…The results of this research are in line with research by Jessica et al, (2023) and Hendri Jopanda (2022) which concluded that the work environment has an indirect effect on job satisfaction through employee work stress, meaning that the better the work environment will reduce employee work stress and increase satisfaction. Work.…”
Section: Working Environment Influences Job Satisfaction Through Work...supporting
confidence: 89%
“…Thus, job satisfaction can negatively or positively impact job stress. Previous research found that job satisfaction has a significant effect on job stress (Tongchaiprasit & Ariyabuddhiphongs, 2016;Xie et al, 2021;Panggabean, 2022;Fitriantini et al, 2020;Jessica et al, 2023;Johan & Satrya, 2023;and Fauziek & Yanuar, 2021). According to Mathis & Jackson (2011) when an employee's expectations are not met, job discontent results.…”
Section: The Relationship Between Job Satisfaction Stress and Life Sa...mentioning
confidence: 98%
“…For example, compensation and benefits, hiring, administration, organizational development, employee motivation, wellness, benefits, safety, communication, performance management, and training are merely dealt by this strategy. The public sector has been experiencing a serious incidence of employees" turnover due to Job dissatisfaction specifically Local Government Authorities and development of the rate of turnover has been increasing day by day Jessica et al [2], Chauhan et al [3], Karatepe et al [4]; Bowling [5]. According to Mehta et al, [6] argued that in business industry the employee retention strategy now days is becoming the top priority of most of organizations due to increasing competition in various businesses.…”
Section: Introductionmentioning
confidence: 99%